2020
DOI: 10.1055/s-0039-3402807
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery Does Not Influence Postpartum Hypercoagulability Measured by Thrombin Generation or Thromboelastometry

Abstract: Introduction Venous thromboembolism (VTE) is a significant cause of maternal mortality with the greatest risk postpartum. Mode of delivery influences VTE risk, with emergency caesarean section (CS) associated with the highest risk (CS). Thromboprophylaxis is recommended for selected women to reduce the risk of VTE.We aimed to investigate the impact of mode of delivery and thromboprophylaxis on hypercoagulability as measured by thromboelastometry (TEM) and thrombin generation (TG) in women at high VTE risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
1
0
3
Order By: Relevance
“…However, emerging data suggest that this is unlikely to be the case. Guimicheva et al [36] reported no difference in thrombin generation between women who had caesarean sections (elective or emergency) and women who had a vaginal delivery, both of whom were receiving thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging data suggest that this is unlikely to be the case. Guimicheva et al [36] reported no difference in thrombin generation between women who had caesarean sections (elective or emergency) and women who had a vaginal delivery, both of whom were receiving thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…La capacidad aumentada de generar trombina, la resistencia adquirida a la proteína C y la activación de la coagulación suponen una ventaja al prevenir la hemorragia materna excesiva (13) , pero a su vez pueden manifestarse clínicamente en el aumento en las tasas de ETEV ya mencionadas. Los estudios de valoración global de la coagulación, tales como la tromboelastometria y el estudio del potencial de generación de trombina podrían constituirse en herramientas útiles para evaluar la hipercoagulabilidad asociada con la gestación (24) . Grafica 2: ETPB AUC2 CAL en cesáreas y partos Abreviatura-ETPB AUC2 CAL: concentración máxima de generación de trombina calculada Existe evidencia de que la vía de finalización del embarazo influye de manera importante sobre el riesgo de enfermedad tromboembólica, presentando las cesáreas de coordinación un aumento al doble en el riesgo con respecto al parto vaginal, y la cesárea de emergencia otro aumento al doble con respecto a la cesárea electiva (24) .…”
Section: Discussionunclassified
“…Los estudios de valoración global de la coagulación, tales como la tromboelastometria y el estudio del potencial de generación de trombina podrían constituirse en herramientas útiles para evaluar la hipercoagulabilidad asociada con la gestación (24) . Grafica 2: ETPB AUC2 CAL en cesáreas y partos Abreviatura-ETPB AUC2 CAL: concentración máxima de generación de trombina calculada Existe evidencia de que la vía de finalización del embarazo influye de manera importante sobre el riesgo de enfermedad tromboembólica, presentando las cesáreas de coordinación un aumento al doble en el riesgo con respecto al parto vaginal, y la cesárea de emergencia otro aumento al doble con respecto a la cesárea electiva (24) . En esta misma línea, el presente estudio plantea evaluar el potencial generador de trombina como una herramienta adicional para estimar ese riesgo.…”
Section: Discussionunclassified
See 1 more Smart Citation